A comparison of the autecology of two seed-taking ant genera, Rhytidoponera and Melophorus - Majer, Jonathan; Gove, Aaron; Sochacki, S.; Searle, P.; Portlock, C. (Birkhauser Verlag, AG, 2011)
Members of the genus Rhytidoponera and, to a lesser extent, certain Melophorus spp. are keystone mutualists for the dispersal of seeds in the southwest of Western Australia, with important ramifications for the ecology and speciation of plants in this biodiversity hotspot. For this reason, it is important to understand the autecology of the relevant ant species and the way in which they interact with plant seeds. This paper addresses key aspects of the ecology of three such ant species, Rhytidoponera violacea (Forel), R. inornata Crawley and Melophorus turneri perthensis Wheeler. Data are presented on their geographic distribution, seasonality of foraging, diurnal activity, response to fire, nest site preference, nest structure, colony size, feeding habits, foraging response to seed availability, and seedling emergence from nests. The role of all three species as seed dispersers is confirmed, and all three species have ecologies that are well-suited for dispersal and survival of native plant seeds. Preservation of this interaction is important for the conservation of plants, and it is fortuitous that all three species are able to survive disturbance and return to rehabilitated areas. However, the smaller R. inornata, and to a lesser extent, the larger R. violacea, are vulnerable to invasive ant [Pheidole megacephala (Fabricius)] incursions. M. turneri perthensis is able to coexist with the invasive ant unless this is at high densities, probably as a result of its ability to forage during high temperatures when the invasive species is inactive.